Experiences of Prejudice, Stereotype, and Discrimination Exposure of Secondary School Students - Onur Guleryuz; Bahadir Kilcan (Anı Publishing, 2023)
Although being exposed to prejudice, stereotype and discrimination reduces the self-esteem and quality of life of individuals, the effect of it on secondary school students is not fully understood. This study aimed to reveal the meaning, structure and essence of secondary school students' experiences of being exposed to prejudice, stereotype and discrimination. The present study was conducted with phenomenology, one of the qualitative research designs. Maximum variety and criterion sampling from one of the purposive sampling strategies were used to determine the participants. In this study, research participants consisted of 12 students studying in 7th and 8th grades in two public schools in Ankara, Turkiye. Research data were collected by semi-structured interview method. Within the scope of this study, 24 in-depth interviews were conducted with each participant twice. In data analysis, phenomenological analysis, bracketing, listing key phrases, developing sets of meanings, textural description, structural description, and extracting essences, were used. The findings showed that the students exposed to prejudice, stereotyping and discrimination suffered from self-esteem and self-confidence, their academic motivation decreased, they developed sympathy for the in-group and antipathy to the out-group and they were in search of equality and justice.